IL-6 Mutation Attenuates Liver Injury Caused by Aeromonas hydrophila Infection by Reducing Oxidative Stress in Zebrafish - Zhai, Wenya; Wang, Zhensheng; Ye, Canxun; Ke, Lan; Wang, Huanling; Liu, Hong (International journal of molecular sciences, 2023)
Interleukin-6 (IL-6), a pleiotropic cytokine, plays a crucial role in acute stress induced by bacterial infection and is strongly associated with reactive oxygen species (ROS) production. However, the role of IL-6 in the liver of fish after Aeromonas hydrophila infection remains unclear. Therefore, this study constructed a zebrafish (Danio rerio) il-6 knockout line by CRISPR/Cas9 to investigate the function of IL-6 in the liver post bacterial infection. After infection with A. hydrophila, pathological observation showed that il-6−/− zebrafish exhibited milder liver damage than wild-type (WT) zebrafish. Moreover, liver transcriptome sequencing revealed that 2432 genes were significantly up-regulated and 1706 genes were significantly down-regulated in il-6−/− fish compared with WT fish after A. hydrophila infection. Further, gene ontology (GO) analysis showed that differentially expressed genes (DEGs) were significantly enriched in redox-related terms, including oxidoreductase activity, copper ion transport, etc. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that DEGs were significantly enriched in pathways such as the PPAR signaling pathway, suggesting that il-6 mutation has a significant effect on redox processes in the liver after A. hydrophila infection. Additionally, il-6−/− zebrafish exhibited lower malondialdehyde (MDA) levels and higher superoxide dismutase (SOD) activities in the liver compared with WT zebrafish following A. hydrophila infection, indicating that IL-6 deficiency mitigates oxidative stress induced by A. hydrophila infection in the liver. These findings provide a basis for further studies on the role of IL-6 in regulating oxidative stress in response to bacterial infections.